Effects of grazing intensity and prescribed fire on soil physical and hydrological properties and pasture yield in the savanna woodlands of Burkina Faso - Savadogo, P.; Sawadogo, L.; Tiveau, D. (2007)
In West Africa policies for prescribed early fire and livestock grazing in the savanna woodlands are rarely based on long-term experimental studies. The inherently different management characteristics and their effects on the vegetation dynamics make landscape degradation a contentious issue. The effects of grazing intensity were investigated by a comparison of non-grazed areas, lightly grazed areas, moderately grazed areas, heavily grazed areas and very heavily grazed areas that received one of two fire treatments: early burning and fire protection in a long-term 12-year study. The parameters assessed reflected changes in herbaceous plant cover, biomass as well as soil physical and hydrological properties. The main findings were by and large specific for the grazing level. This supports the argument for devolution of management responsibility to the local level where there is indigenous site-specific knowledge but at the same time insufficient management capacity. A comparison of composite soil samples taken at a depth of 0–10 cm did not differentiate significantly between treatments. This is probably because the composite soil sampling procedure hid the properties of the top first few centimeters. Grazing pressure had a tendency to reduce total above ground biomass (p = 0.081). This was related to increased biomass removal and the trampling pressure (static load) exerted by the animals. The infiltration measurements indicated that the deleterious impact of cattle trampling increased as stocking rate increased. Livestock grazing significantly (p = 0.038) lowered the infiltrability. Prescribed early fire had a tendency (p = 0.073) to reduce the soil water infiltration rate. The subplots subjected to prescribed burning had a lower steady state infiltration rate compared to unburnt areas (means of 49.2 ± 27.5 mm h-1 versus 78 ± 70.5 mm h-1 for burnt and unburnt subplots, respectively). A partial least squares projection to latent structures showed that 34% of the steady state infiltrability was explained by the stocking rate and soil organic matter. Also all soil characteristics were significantly connected to steady state infiltrability suggesting that they are related to the soil hydrological response to trampling. From a management perspective, adoption of a short duration grazing system should avoid high stocking rates because they may adversely affect soil infiltrability, increase susceptibility to erosion in the savannas and decrease biomass productivity.